The three-dimensional morphology of the Antarctic ozone minimum - Aikin, A. C.; Mcpeters, R. D. (1988)
The three-dimensional morphology of the Antarctic ozone minimum was obtained by mapping ozone distribution data from Nimbus-7 solar backscatter UV instrument, obtained at different pressure levels, on a south polar projection. These maps show that a clearly defined ozone minimum relative to the local ozone field extends throughout the stratosphere from about 10 km to above 50 km, though the intensity of the ozone decrease becomes less with altitude. The examination of the behavior of the general ozone-hole area suggests the existence of at least three distinct regions: (1) the region below 33 km, where ozone follows the pattern of the ozone hole, exhibiting a strong trend since 1979 and decreasing from late August to a minimum in October; (2) the 33-43 km height region of relatively stable ozone concentration; and (3) the region above 43 km, where ozone is again fluctuating, with a decrease during September to a minimum in October.